Pulmonary Hypertension in Pregnancy - Banerjee, Debasree; Ventetuolo, Corey E. (Seminars in Respiratory and Critical Care Medicine, 2017)
Pulmonary arterial hypertension (PAH) is a pulmonary vasculopathy associated with abnormal cardiopulmonary hemodynamics and a limited life expectancy due to right heart failure. Young women are preferentially affected. Women with PAH are at increased risk of complications and death during pregnancy for both the mother and the fetus. While it is not well characterized how changes in sex steroids and other hormones during pregnancy affect pulmonary hypertension, many expected systemic and heart–lung physiologic adaptations during gestation are poorly tolerated in women with PAH. Despite the approval of numerous therapies for PAH in recent years, pregnancy avoidance or early termination is still recommended in women with PAH because of poor outcomes. In this review, we will discuss physiologic and hormonal changes in pregnancy as they relate to pulmonary vascular disease and right heart function. We will review current consensus recommendations and outline the management of pregnancy in PAH when it does occur.
Keywords: pulmonary hypertension; pregnancy; right heart failure